2012
DOI: 10.3390/molecules17078471
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Activity of Constituents from Foeniculum vulgare Var. Dulce Grown in Mexico

Abstract: Bioassay guided fractionation of an antimycobacterial extract of Foeniculum vulgare var dulce (Apiaceae) led to the isolation and characterization of 5-hydroxyfurano-coumarin. The chemical structure of this compound was elucidated by 1 H and 13 C (1D and 2D) Nuclear Magnetic Resonance (NMR) spectroscopy. In addition, the active fractions were analyzed by GC-MS and seventy eight compounds were identified; the major compounds were 1,3-benzenedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Limnophila geoffrayi Bon., Scrophulariaceae, a common ingredient in northeastern Thailand curry, is an antipyretic, expectorant, and a lactogogue. The antimycobacterial compounds nevadensin (45) and isothymusin (46) were reported from the chloroform extract of the above plant through bioassay-guided fractionation and the compounds were safe to use as evidenced from a mutagenic assay [29]. Pelargonium reniforme Spreng., Geraniaceae, of Africa is being used in the treatment of various ear, nose, and throat infections, and the main constituent of the tuberculosis remedy in the extract is known as "Umckaloabo".…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Limnophila geoffrayi Bon., Scrophulariaceae, a common ingredient in northeastern Thailand curry, is an antipyretic, expectorant, and a lactogogue. The antimycobacterial compounds nevadensin (45) and isothymusin (46) were reported from the chloroform extract of the above plant through bioassay-guided fractionation and the compounds were safe to use as evidenced from a mutagenic assay [29]. Pelargonium reniforme Spreng., Geraniaceae, of Africa is being used in the treatment of various ear, nose, and throat infections, and the main constituent of the tuberculosis remedy in the extract is known as "Umckaloabo".…”
mentioning
confidence: 99%
“…Adhatoda vasica Ness., Acanthaceae, which is used in the treatment of colds, cough, and other respiratory disorders, contains antimicrobial compounds. Alkaloids present in the hexane extract like vasicine acetate (1) and 2-acetyl ben- [21] dihydroguaiaretic acid (50 µg/mL) (12.5-50 µg/mL) [28] pisonin B (25 µg/mL) [32] falcarindiol (26.7 µg/mL) [65] 2′-nortiliacorinine and tiliacorine (3.1 µg/mL) (3.1 µg/mL) [12] pinocembrin (3.5 µg/mL) [18] (E)-3,2′,4′-trihydroxy-3′-methoxychalcone (174.8 µM) [21] 4-epi-larreatricin (50 µg/mL) (25 µg/mL) [28] [33] licarin A (25 µg/mL) (3.12-12.5 µg/mL) [42] linoleic acid and oleic acid (100 µg/mL) (100 µg/mL) [46] 1,3 dimethoxy-2-methyl-5-pentyl benzene (≤ 2.5 µg/mL) [66] 13′-bromo-tiliacorinine (3.1-6.2 µg/mL) (1.5-3.1 µg/mL) [12] kanzanol C, 4-hydroxylonchocarpin, stipulin, and amentoflavone (9.76 -> 39.06 µg/mL) [19] aminoacetate derivative of diospyrin (> 10 -≤ 50 µg/mL) (> 10 -≤ 50 µg/mL) [34] licarin B (50 µg/mL) (12.5-50 µg/mL) [42] undecanal (100 µg/mL) (50-200 µg/mL) [46] 3-methoxy-2-methyl-5-pentyl phenol (≤ 2.58 µg/mL) [66] Mauritine M (IC 50 − 72.8 µM) [13] genistein (35 µg/ml) [20] diospyrin (100 µg/mL) (100 µg/mL) [34] eupomatenoid-7…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The biotransformation with Saccharomyces cereviceae of 9-methoxytariacuripyrone, a natural compound isolated from A. brevipes, yielded 9-amino-9-methoxy-3, 4-dihidro-2H-benzo[h]-cromen-2-one which also showed a MIC= 3.12µg/mL. It is necessary further to evaluate the intracellular activity and cytotoxicity of the most active extracts and compounds; however, the potential for finding new therapeutically leads exists, especially against strains resistant to common drugs (Encarnación-Dimayuga et al 2006, Esquivel-Ferriño et al 2012, Gould 2009, Gurinder and Daljit 2010, Jiménez-Arellanes et al 2007, Levy and Marshall 2004, Molina-Salinas et al 2011, Sandoval-Montemayor et al 2012, Rajandeep et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the presence of compounds such as, linoleic acid, undecanal, 1, 3-benzenediol, oleic acid and 2, 4-undecadienal in the extract. It is reported that fennel seed extract contain 5-hydroxy-furanocoumarin which contributes in antimicrobial property of this plant [15].…”
Section: Discussionmentioning
confidence: 99%